JUAL BELI HARTA WARISAN YANG BELUM DIBAGI MENURUT ADAT DAN PERSPEKTIF HUKUM ISLAM (STUDI KASUS DI DESA RANTAU MACANG) - Thoiyibi, M. (Sosio Akademika, 2024)
This research was carried out with the aim of finding out how to buy and sell inherited property that has not been divided in the village of Rantau Macang based on Customary Law and Islamic Law. It was known in the preliminary research that the sale and purchase of inherited property was unilateral, which occurred in one family consisting of five brothers. And according to the custom of Rantau Macang Village, the sale of inherited property that has not been distributed is sanctioned by replacing the same item or property as sold. In order to reveal this, research has been carried out with a Qualitative approach using methods of gathering power in the form of observations, interviews and documentation, which are then analyzed using descriptive analysis techniques. The results of the research found that the sale of undivided inheritance in the Macang Village Village occurred in several families, from the sales results not being known to all members of the family so that they were not distributed equally to all family members, although this still maintains good relations between families.